2021
DOI: 10.21608/ejhc.2021.194365
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parent Training regarding Coping Strategies on Reducing Stress among Parent of Children with Autism Spectrum Disorder

Abstract: Background: There is no doubt that the mothers' adaptation helps improve the quality of life, not only for any child with special needs but for the whole family, which greatly helps in improving the child's condition and improving the care provided to him by a conscious parent who can meet the child's needs properly. The present study aimed to evaluate the effect of parent training regarding coping strategies on reducing stress among mothers of children with autism spectrum disorder (ASD). Research design: A q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Nevertheless, the lower mean scores of coping of these parents compared to the present research may be due to usage of different instruments and fewer mothers participating in this study. Meanwhile, the study by Sabra Ahmed et al (2021) showed that the parents of autistic children have low coping levels, and usually employ inefficient and negative coping strategies, where training coping strategies were effective in enhancing the coping of mothers raising children with autism (Ahmed et al 2021b). The coping scores of mothers of autistic children in this study were lower than in the present research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the lower mean scores of coping of these parents compared to the present research may be due to usage of different instruments and fewer mothers participating in this study. Meanwhile, the study by Sabra Ahmed et al (2021) showed that the parents of autistic children have low coping levels, and usually employ inefficient and negative coping strategies, where training coping strategies were effective in enhancing the coping of mothers raising children with autism (Ahmed et al 2021b). The coping scores of mothers of autistic children in this study were lower than in the present research.…”
Section: Discussionmentioning
confidence: 99%
“…According to Table 6, the factor of coping followed by quality of life of mothers were the most important predictor factors for that self-care performance in autistic children. In this regard, Sabra Ahmed (2021) showed that increased adaptation of mothers in the family enhances not only the ability of the mother, but also that of the other family members involved in providing care issues and training daily skills for fulfilling the child's needs (Ahmed et al 2021b). Also, the study by Selvakumar and Panicker (2020) showed that coping of parents was effective for their participation in training the child and thus improving the self-care performance of the child.…”
Section: Discussionmentioning
confidence: 99%
“…key words: Mindfulness-Psychological stress-Life satisfaction -Mothers of Autism Spectrum Disorder. (Kholidah,et,al.,2018;Miranda,et,al.,2019;Magor,et,al.,…”
mentioning
confidence: 99%